Wakeboarding complex an out of the pit recreational development - Arellano, Marvin Patrick N.; Joson, Gerard Thomas F. (Quezon City College of Architecture, University of the Philippines Diliman, 2015)
In the Philippines, Wake Park, a facility that offers wakeboarding activity as it's research it was found out that the wakeboarding operational all throughout the year. Although in this research it was found out that the wakeboarding operation stops during increment weather conditions - extreme rain and extreme heat. Given this condition, this thesis seeks to propose the first wakerboarding facility that can offer an all year round service in the Philippines. Since there are only limited information about wakeboarding, the researcher then used two methods to obtain data and these are through literature review, where it gives information about the facilities site is obtained to be able to create a proper design for the wakeboarding complex. Finally, to be able to successfully solve the problem of this thesis, the researcher literally use and translated the design concept of shaded structure and non-exclusivity to create a different venue that shelters wakeboarding recreational facilities.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Sports facilities -- Designs and plans; Wakeboarding Complex